Enactive cognitive science: revisionism or revolution?. (June 2013) - Villalobos, Mario
The enactive approach is usually associated with a revolutionary project that aims to transform in a radical way our understanding of mind and cognition. Bold theoretical moves such as the rejection of cognitive representations or the assumption of a deep continuity between life and mind, among other enactive ideas, justify this perception. Nonetheless, when we assume a broader historical perspective, including the long cybernetic tradition that preceded the emergence of cognitive sciences, the image of the enactive approach looks different. Put in the context of the paradigmatic shift that took place between first-order and second-order cybernetics, especially in the case of Maturana's autopoietic theory, the enactive paradigm, so I will try to show in this work, appears rather like a conservative or revisionist project. Better said, it appears as a slightly hybrid paradigm, wherein original and progressive elements coexist with revisionist components. The paper aims to offer an alternative interpretation of the enactive approach and contribute to a better understanding of its identity as a research program, its present and its possible future challenges.